Microbiology and Aging Clinical Manifestations - Percival, Steven L. (Humana Press : Imprint: Humana, 2009)
The microbiological burden on an aging host is enormous, and clinically significant. As humans are living longer there is a greater propensity to infection. This risk is substantially heightened in elderly individuals who are predisposed to infection. Do the microbiological changes that occur within and upon the host influence the process of ageing or is it the biological changes of the host that affects the host's microbiology? Do such changes therefore affect the host's propensity to disease? Are there ways of enhancing life expectancy by reducing certain bacteria from proliferating or conversely by enhancing the survival of beneficial bacteria? Microbiology & Aging: Clinical Manifestations encompasses a collection of reviews that highlight the significance of, and the crucial role, that microorganisms play in the human life cycle and considers the microbiology of the host in different regions of the body during the aging process.